Alleviating workplace stress: the role of servant leadership in preventing productivity decline among Pakistan’s private higher education institutions - Warda Naseem; Hamid Mahmood; Abdul Rauf; Yuen Yee Yen (Cogent Business & Management)
Stress altruistically disrupts employee productivity in private educational institutions, and there is an observed association between knowledge hiding and stress factors among employees despite the remedial role of servant leadership. Present study examines the impact of stress on employee productivity in private educational institutions, explores its association with knowledge hiding, and evaluates the role of servant leadership in alleviating stress and reducing knowledge hiding practices. The researcher employed a convenience sampling technique to collect data from 613 academicians through paper survey who working in higher education institutions in southern Punjab, Pakistan. The collected data were analyzed through AMOS version (25.0) for path analysis. The findings revealed that stress factors predicted employee altruism and supplementary stimulates productivity and servant leadership reinforces the association between knowledge hiding and employee productivity. The present research sheds light on how and whereupon stress factors affect employee productivity, with inferences for private administration enactments and encouraging productivity. The findings offer practical insights for managers to reduce stress-induced productivity losses and knowledge hiding through servant leadership, while the research contributes theoretically by exploring altruistic stress dimensions and emphasizing the moderating role of servant leadership in enhancing knowledge sharing.